The relationship between visual function and performance in rifle shooting for athletes with vision impairment - Myint, J.; Latham, K.; Mann, D.; Gomersall, P.; Wilkins, A. J.; Allen, P.M. (BMJ Open Sport & Exercise Medicine, 2016)
Background: Paralympic sports provide opportunities for those who have an impairment that might otherwise be a barrier to participation in regular sporting competition. Rifle shooting represents an ideal sport for persons with vision impairment (VI) because the direction of the rifle can be guided by auditory information when vision is impaired. However, it is unknown whether those with some remaining vision when shooting with auditory guidance would be at an advantage when compared with those with no vision at all. If this were the case then it would be necessary for those with and without remaining vision to compete in separate classes of competition.